Assessing the Level of Employees' Sustainability Awareness and its Effect on Sustainable Development Progression - A Case Study of Greater Karak Municipality/ Jordan - Sara El-Shqeirat (Environmental Science and Sustainable Development)
The current discourse on Sustainability Awareness (SA) is mainly focused on offering employees environmental training and education that aims to increase their participation in the organization's sustainable progress. Hence, overlooking the importance of the SA policy-making phase as well as the critical role designing SA programs plays in activating employees' efficient contribution to sustainability initiatives. Therefore, the significance of this research lies in offering an alternative model that integrates both processes of measuring and raising SA with the prospect of altering the organization's culture where sustainability value is created to motivate employees' engagement. In addition, this research will justify the failure of cases where environmental education, training, and SA programs did not positively affect employees' engagement nor did they benefit the organization's sustainable progress. This research presents organizations and decision-makers with a new approach to raising SA levels aiming to increase the potential for effective employment of the newly acquired knowledge. Hence, makes sustainable achievements more tangible. This model suggests the use of a qualitative approach to measuring employees' SA levels; a model that includes collecting data on employees'  insights, conceptions, sources of knowledge, and personal experiences of sustainability. This model would replace the commonly used quantitative approach to measure SA which is limited to analyzing data numerically to draw a statistical picture aiming to determine whether a pre-designed SA program should be implemented. Instead, managers could benefit from the data collected in the SA measuring process to identify the focus areas of the SA-raising program. Furthermore, such data would help organizations design SA programs that are specifically tailored to target a change in their employees' mindset and beliefs.